2012
DOI: 10.1111/j.1365-2702.2011.03880.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of issues of ethnicity and culture in nursing homes in an English region: nurse managers’ perspectives

Abstract: Nursing homes in England are increasingly diverse communities, and staff training needs must be addressed to promote quality care for all residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…However, Gerrish et al [43] have highlighted that both nursing personnel and doctors need training in how to collaborate with interpreters, so the communication can run smoothly between the triad of patient, professional and interpreter. Other ways to aid communication with minority ethnic groups in health care has been described such as including family members who can translate and write down usable words and phrases [44] , or using multilingual staff in nursing homes [45] . Samarasinghi and co-workers [28] suggested a family-focused care with a supportive conversation with the members of the family as a means of improving the care of immigrants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Gerrish et al [43] have highlighted that both nursing personnel and doctors need training in how to collaborate with interpreters, so the communication can run smoothly between the triad of patient, professional and interpreter. Other ways to aid communication with minority ethnic groups in health care has been described such as including family members who can translate and write down usable words and phrases [44] , or using multilingual staff in nursing homes [45] . Samarasinghi and co-workers [28] suggested a family-focused care with a supportive conversation with the members of the family as a means of improving the care of immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with what Gerrish and co-workers [43] reported, and they also found that professionals in health-care were reluctant to use interpreters in the encounter with minority ethnic groups. Even if the presence of family members is important for supporting older immigrants in their contact with the health care system [44] , the utilization of professional interpreters is also of outmost importance [37] . However, Gerrish et al [43] have highlighted that both nursing personnel and doctors need training in how to collaborate with interpreters, so the communication can run smoothly between the triad of patient, professional and interpreter.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanatory factors include expectations among family carers that services will be culturally inappropriate (in terms of language and food), and a greater sense of filial piety and obligation . Care home staff have reported challenges providing culturally appropriate care, for example appropriate diets and translation services, and in day to day communication . With the number of BME care home residents with dementia projected to increase due to demographic trends, it is important to consider how care homes can best provide culturally competent care.…”
Section: Introductionmentioning
confidence: 99%
“…It is also likely that some of the problems of trials in these patients—such as the assessment of side-effects—would be best moderated by the ability of staff to withdraw assent if necessary. However, the increasing heterogeneity of ethnicity and culture among staff and residents in care home settings (ref Badger)12 may interfere with this process, especially if there are significant language barriers, as will low levels of understanding and recognition of dementia (Macdonald and Carpenter,13 Macdonald and Woods) 14. Qualified care staff may not know the patients as well as unqualified care workers, but the latter are among the lowest paid15 and poorly educated and trained16 employees in the UK.…”
Section: Discussionmentioning
confidence: 99%